Robust autopilot design for landing a large civil aircraft in crosswind - Theis, Julian; Ossmann, Daniel; Thielecke, Frank; Pfifer, Harald (Elsevier, 2018)
A comprehensive autolanding design for a representative model of a twin-engined commercial aircraft is presented in this paper. To facilitate the design task and minimize control law switching, a cascaded control structure is selected which resembles integrator chains. Classical loopshaping and robust control techniques are used to design the individual control loops. The emphasis is on providing a complete and comprehensive qualitative design strategy. The control system’s ability to safely land the aircraft despite strong crosswind in a variety of possible scenarios is demonstrated in an industry-grade verification campaign. Nonlinear Monte Carlo simulations of the airliner model are used to assess the risk of unsafe landing conditions and provide insight into the performance characteristics and limitations of the proposed control system.